Pengaruh Desain Fasad Terhadap Waktu Melalui Analisa Jarak Pandang dan Suhu Ketika Terjadi Kebakaran - Ghaitsa Shahira Shafa; Debby Seftyarizki; Panji Anom Ramawangsa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As a place of worship for Muslims and a place of study for other religions, mosques are buildings that really need to be considered in mitigating fire disasters. Apart from that, there is not much research that discusses fire safety in mosque buildings. So, this research was carried out in which the main focus of the research was on the fire safety of mosque buildings through scenario simulations of different facade shapes, namely in scenario 1 using the existing conditions with the first layer of the facade. Furthermore, in scenario 2, using the outermost facade layer according to the existing conditions and removing the first layer of the facade, namely the walls covering the inner area of the mosque, and scenario 3 uses the author's facade design in the form of calligraphy. The simulation was carried out using fire simulation software, namely PyroSim. In the scenario studied the heat release rate/area was 750 kW/m² which lasted for 300 seconds. In the scenario described, it shows that scenario 3 has a longer ASSET (Available Safe Egress Time), namely at visibility it takes 300> seconds and at temperature 300 seconds. This facade has a more powerful air flow than the other two scenarios so that smoke and temperature can be minimized through this air flow